2010
DOI: 10.1007/s10803-010-1087-7
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function Mechanisms of Theory of Mind

Abstract: This study examined the relationship between Executive Function (EF) and Theory of Mind (ToM) using the Delis-Kaplan Executive Function System (D-KEFS) and three tests of ToM (Reading the Mind in the Eyes test (RMET), Strange Stories test, and Faux Pas test). Separate regression analyses were conducted, and EF predictors varied by ToM test. No EF domains accounted for significant variance in RMET scores; only estimated IQ scores were significant predictors of RMET performance. Verbal fluency and deductive reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
131
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(156 citation statements)
references
References 55 publications
19
131
3
3
Order By: Relevance
“…For example, Bosacki [41] observed that female preadolescents were better than their male counterparts on the intrapersonal task of constructing a coherent sense of self and on the interpersonal task of understanding multiple and contradictory intentions of others. More recently, other authors also verified that women performed better in the FP test than men [42]. Hence, our results seem to support the sensibility of the FP Recognition Test (namely, the FP-det) to discriminate female superiority in recognizing and inferring mental states and predicting behavior in others.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Bosacki [41] observed that female preadolescents were better than their male counterparts on the intrapersonal task of constructing a coherent sense of self and on the interpersonal task of understanding multiple and contradictory intentions of others. More recently, other authors also verified that women performed better in the FP test than men [42]. Hence, our results seem to support the sensibility of the FP Recognition Test (namely, the FP-det) to discriminate female superiority in recognizing and inferring mental states and predicting behavior in others.…”
Section: Discussionsupporting
confidence: 86%
“…Poor social cognition skills in late adolescence or early adulthood can impede educational and vocational success and friendship formation potentially leading to isolation, anxiety and depression (Ahmed & Miller, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this was the first study to investigate cognitive ToM performance in a Chinese clinical high-risk population and to report FP performance in a group of individuals at CHR compared with that in HCs. Compared to other ToM tests, such as the Strange Stories Test [21] and Facial Emotion Identification Test (FEIT) [25], the FPT appeared to be more complicated for participants as they need to understand the beliefs of two characters simultaneously [2,20], which may be more susceptible to the identification of ToM deficits in individuals with prodromal psychosis. Meanwhile, some non-social cognitive functions, such as attention and working memory, were positively associated with ToM performance among participants in the prodromal stage of psychosis.…”
Section: Discussionmentioning
confidence: 99%